Islamisation of engineering education – a case at IIUM - Mamun, Abdullah Al; Muthalif, Asan G. A.; Ahmad, Zuraida; Ismail, Ahmad Faris; Ismail, Kamsiah; Maleque, Md. Abdul (Horizon Research Publishing, 2020)
Seeking knowledge and continuing education are very important elements in Islam. All Muslims (both male and female) are required to make sincere efforts to acquire knowledge for the benefits of themself and the society; They believe that there is only one God (Allah) and He is the ultimate source of all knowledge. Although the education system has various branches, this paper is intended to present the common issues related to the Islamic values and practices in engineering education and the ways to instil ethics & spirituality into the technical education system. The step by step initiatives taken by the faculty of engineering at the International Islamic University Malaysia (IIUM) is highlighted in this paper. In order to achieve the goals of Islamisation of engineering education at IIUM, the relevant Islamic elements are added into the curriculums, textbooks are written and learning outcomes are set (at IIUM) to assess the student’s ability in appreciating the link between the revealed and acquired knowledge. Generally, such initiatives are welcomed by the students, though it requires a substantial amount of continuous efforts from the academic staffs. It is realised that Islamisation of the engineering education and continuous reminder of spirituality in engineering practices are essential to reduce the corruption and unethical practices in the engineering profession, which is one of the major socio-economic problems in many countries, rich or poor, developed or developing. Steps taken in the engineering curriculum design is part of the faculty’s initiatives to achieve its vision, which is to be a world-class centre for engineering education and research with values and ethics. Information shared in this paper could be beneficial for both secular and non-secular education system.